Law Enforcement of Waste Management in An Effort to Reduce Flood Risk in Indonesia - Azhar Azhar; Kgs Muhammad Sobri; Abdul Halim (Jambe Law Journal, 2020)
The aim of this paper is to identify law enforcement of waste management and formulate a law enforcement model for urban waste management in an effort to reduce flood risk. The explanatory survey was used in this study. Quantitative and qualitative approaches were used to explain the relationship between several variables. Sampling techniques were carried out in stages, and proportionally according to the research objectives. Besides, the data collection in this study carried out through observation, in-depth interviews, documentation and audio visual. The data analysis technique used descriptive qualitative through an interactive model developed by Miles and Huberman consisting of four interacting components, namely data collection, data reduction, data presentation and drawing conclusions and verification. Results indicate that there are some issues in law enforcement of waste management. First, the total number of law enforcers is not enough. Second, there are lack of facilities and infrastructures such as garbage cans, collection, temporary landfills, transportation and final processing. Third, there is a lack of commitment by the authorities in enforcing waste management laws related to reducing the risk of flooding. Furthermore, public awareness to comply with waste management is very law. Finally, there is still a lack of public awareness of the risk of flood. In conclusion, almost half of the community is aware that disposing of garbage in its place is very important for their survival and flood risk in their area. On the other hand, half of the people who do not care and still throw waste not properly